Probable acute disseminated encephalomyelitis due to Haemophilus influenzae meningitis - Beleza, P (2012)
We report the case of a 17-year-old male on long-term steroid therapy for minimal lesion glomerulopathy who, after an upper respiratory infection, presented with Haemophilus influenzae type b meningitis. Twenty-four hours later he developed depression of consciousness which progressed to coma and left hemiparesis. Brain magnetic resonance imaging (MRI) revealed multiple lesions (hyperintense on T2 and slightly hypointense on Tl) involving mainly white matter suggestive of inflammation. MRI features were compatible with acute disseminated encephalomyelitis (ADEM), although a differential diagnosis included cerebritis or vasculitis, secondary to bacterial meningitis. The patient was treated with high-dose steroids which resulted in a gradual improvement followed by complete clinical recovery. We propose a diagnosis of ADEM was the best diagnosis because of the radiological features and response to steroids. The occurrence of ADEM associated with acute meningitis, however rare, represents an important diagnostic challenge for the clinician.